PENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN JIGSAW - Tri Satria; Luvy Sylviana Zanthy (Journal on Education, 2019)
The purpose of this study is to improve the activities and student learning outcomes through the Jigsaw learning model. This type of research is Class Action Research (CAR). The subjects of this study were teachers and eighth grade students of SMP N 2 Batujajar in the first semester which amounted to 34 students. The method of data collection is done through interviews, observation, tests and documentation. Data analysis techniques use methods that include data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate an increase in activity and learning achievement in mathematics. this can be seen through the following indicators: the ability to express thinking ideas during teaching and learning activities is 10 students (29.40%) after the action became 26 students (76.40%). activeness of asking the teacher in teaching and learning activities there were 9 students (26.40%) after the action became 28 students (82%). the ability to discuss with the study group there were 13 students (38.20%) after the action became 30 students (88.20%). students who have grades fulfilling KKM (≥75) there are 12 students (35.20%) after the action became 29 students (85.20%). The conclusion of this study is that the jigsaw learning model can improve the mathematics learning activities and achievements of class VIII students of SMP N 2 Batujajar Semester I.